Factores determinantes en las OPI (Determining Factors in Initial Public Offers) - Rodríguez, M. P.; Treviño, E.; Cortez Alejandro, Klender Aimer (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. The effect of “underpricing” is closely related to the difference of the price set up in the IPO and the closing price of its first day of trading. This concept has been studied internationally for more than 3 decades and it is lately relevant to emerging countries, particularly in the stock markets in which double digit growth has been an important factor such as the Mexican Stock Market. Here we will find some theoretical studies as well as some behaviors in this matter regarding companies in their first public offer. This article does not pretend to be exhaustive but to bring relevance of several studies and theories, to relate variables in international context to the Mexican Stock Market. Further more, conclusions and follow-up actions in this investigation will aim to have a successful initial public offer.